Analisis konsentrasi dan kemurnian Deoxyribo Nucleic Acid (DNA) dari rumput pakan ternak - Syafiradewi Yulianti; Romi Zamhir Islami; Mansyur; Estria Furry Pramudyawardani (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
This research was conducted at the Biotechnology Research and Testing Lab of the Faculty of Animal Husbandry, Padjadjaran University, and the Rice Standard Instrument Testing Center (BBPSI Padi), Subang Regency, West Java starting on September 20 to December 22, 2023. The purpose of this study was to evaluate the effectiveness of the hipure Kit in isolating grass Deoxyribo Nucleic Acid (DNA) by ensuring adequate concentration and cleanliness of samples from contaminants for subsequent molecular applications. The ideal DNA concentration for PCR is 20-50 ng/µL, with an A260/A280 absorbance ratio of about 1.8-2.0 and an A260/A230 ratio above 2.0, indicating the absence of contamination from proteins, salts, carbohydrates, or other organic compounds. The methodology of this study was a descriptive exploration involving descriptive statistical analysis to evaluate the variation in DNA concentration between samples, using spreadsheet software to facilitate data management. The results of the Nanodrop spectrophotometric analysis showed that there variations in DNA concentration between samples, but generally within a range adequate for laboratory applications such as PCR and sequencing. In addition, the HiPure Plant DNA Kit proved effective in producing high-concentration DNA with clear and defined DNA bands in electrophoresis and effectively minimizing contaminants. Further optimization of the extraction protocol, such as adjusting the incubation time or buffer concentration, is recommended to improve DNA concentration and purity. This step will ensure higher DNA quality for downstream applications such as PCR.